A Prospective Study of the Prevalence of Parkinsonism in Patients With Liver Cirrhosis. Issue 2 (26th November 2020) - Apetauerova, Diana; Hildebrand, Peter; Scala, Stephanie; Zani, Janet W.; Lipert, LeeAnne; Clark, Erin; Fennell, Tanya; Gordon, Fredric D.
Abstract : Acquired hepatocerebral degeneration refers to a neurological syndrome consisting of various movement disorders and cognitive impairment in advanced liver cirrhosis or portosystemic shunt. Neurological signs and symptoms may be attributed to the accumulation of toxic substances in the brain. The most common neurological presentation of this is parkinsonism. Our prospective study aimed to investigate the prevalence of parkinsonism in patients with cirrhosis who were evaluated for liver transplant and to identify any correlation between findings on brain magnetic resonance imaging (MRI) and severity of parkinsonism. Of the 120 enrolled participants with liver cirrhosis, 62 (52%) exhibited signs of parkinsonism and all had MRI basal ganglia hyperintensity. Eighteen patients from this group were transplanted and showed statistically significant improvements in their Unified Parkinson's Disease Rating Scale (UPDRS) scores. Conclusion: The data suggest the reversibility of the neurological impairment seen in cirrhosis, and therefore the effectiveness of transplantation in improving parkinsonian symptoms. There was no correlation between severity of MRI findings and clinical motor UPDRS part III. Laboratory findings showed no correlation among the abnormal levels, MRI brain signal abnormality, or UPDRS scores.